Analisis Kebijakan Pemerintah Tentang Zakat Sebagai Upaya Meningkatkan Perekonomian Indonesia Pasca Reformasi Tahun 1998 - fathurrahman, muhammad rifqi; Nursaadah , Intan (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2023)
Zakat is a mandatory worship for Muslims. In addition to having religious values ​​for individuals who carry it out, zakat is an Islamic financial instrument that has the potential to help improve the community's economy. Since it was first prescribed by Islamic state and sultanate leadership, the implementation of zakat has had a major impact on the country's economic development. Judging from the implementation potential that must be issued every certain period and the amount issued depending on everyone's opinion, the potential for a large amount of zakat. This potential has been realized by the government, especially after the monetary crisis that occurred in 1998, this can be seen from the issuance of Law No. 38 of 1999 concerning the management and utilization of zakat. Then made several improvements and revisions until Law No. 23 of 2011 was issued. This shows that the government sees zakat as a Muslim worship that can help improve the country's economy by regulating mechanisms, management of its distribution and utilization. This study aims to analyze the government's paradigm regarding zakat in its statutory regulations; find out how the government responds to the potential of zakat for Muslims to collaborate in developing the country's economy; and knowing how the problematic management of zakat is seen from the issuance of laws historically.